Achievement and Behavior in Charter Schools: Drawing a More Complete Picture - Imberman, Scott A. (The Review of Economics and Statistics, 2011)
I use a long panel with broad grade coverage to establish whether charter schools affect cognitive and noncognitive skill formation. Schools that begin as charters generate large improvements in discipline and attendance but not test scores, with the exception of math in middle schools. This suggests improvements in noncognitive but not cognitive skills, although these improvements do not persist if students return to regular public schools. Charters that convert from regular public schools have little impact on either skill type. These results are robust to potential biases from selection off of precharter trends, attrition, and persistence. © 2011 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.